Damage-chemo-viscoelastic model on the analysis of concrete dams under swelling processes - Piteira Gomes, J. (2009)
The analysis of the observed behaviour and the structural safety control of concrete dams under swelling processes, namely due to alkali-silica reactions (ASR), require the use of appropriate mathematical models, generally supported by the finite element method. These models must take into account the factors that influence the development of swelling processes, namely the concrete properties, the environmental conditions (temperature and humidity) and the stress field in the structure, as well as the over-time changes in the rheologic properties of materials and the damage induced by swelling. This purpose was achieved by a damage-chemo-viscoelastic model, based on a constitutive isotropic damage law, which consider that the evolution of the damage variables (both tensile and compressive) depends exclusively on elastic strains. The concrete time behaviour was taken into account by an incremental constitutive relation corresponding to a Kelvin chain. The hypothesis of isotropic material with a time variable elasticity modulus and a constant Poisson ratio was admitted. The free-stress swelling process is assumed to be isotropic and the influence of the stress field was also considered. This model makes it possible to compute displacements, strains, stresses and damage over time. This paper is to present the main features of the mathematical models developed and the results of its application to the analysis of the observed behaviour of an approximately 60- years old Portuguese buttress dam, the Pracana dam, which has been subject to a concrete swelling process due to ASR.